Molecular detection of Hepatozoon spp. and Cytauxzoon sp. in domestic and stray cats from Madrid, Spain - Díaz Regañon, David; Villaescusa, Alejandra; Ayllón Santiago, Tania; Rodríguez Franco, Fernando; Baneth, Gad; Calleja Bueno, Lydia; García Sancho, Mercedes; Agulla, Beatriz; Sainz, Ángel (My University, 2017)
Background: Different species of apicomplexan protozoans of the genera Hepatozoon and Cytauxzoon can infect domestic cats, but their epidemiology and clinical relevance are not fully understood. The aim of this study was to assess the molecular prevalence of Hepatozoon spp. and Cytauxzoon spp. and to identify associated risk factors and clinical and laboratory abnormalities in a population of cats from Madrid, Spain. Methods: Six hundred and forty-four client-owned and stray cats from Madrid, Spain, were included in this study. DNA samples were analyzed by two polymerase chain reaction (PCR) tests to detect a partial sequence of the 18S rRNA gene of Hepatozoon spp. and Cytauxzoon spp. In order to evaluate possible associations between infection by these protozoans and epidemiological or clinical parameters, data were collected related to: the season of sample collection, age, gender, spayed/neutered status, breed, living area, lifestyle, outdoor access, contact with other animals, prey on wild animals, history of tick or flea infestation, travel history, ectoparasiticide treatment, previous blood transfusion, previous tetracycline administration in the last 60 days, Feline Leukemia virus (FeLV) and Feline Immunodeficiency virus (FIV) status, positivity to other vector-borne diseases, the presence or absence of clinical signs and hematological or biochemical alterations. Results: DNA of Hepatozoon spp. and Cytauxzoon sp. was amplified from the blood of 10 (1.6%) and 8 (1.2%) cats, respectively. Previous treatment with tetracyclines in the last 60 days, previous administration of blood transfusion, a decrease in haematocrit and an increase in creatinine were associated with Hepatozoon spp. infection. Cytauxzoon sp. infection was more frequent in samples collected during the winter months and in cats living in rural areas. This infection was associated with a FIV-positive status. Some of the cats that were positive for Hepatozoon spp. or Cytauxzoon sp. had been exposed to other vector-borne pathogens, such as Ehrlichia canis and Bartonella henselae. Conclusions: Our results indicate that cats from Madrid, central Spain, are infected with Hepatozoon spp. and Cytauxzoon sp., although with a low prevalence. Further studies are needed to determine the virulence of these agents in Spanish cats. Keywords: Cat, Central Spain, Cytauxzoon sp., Hepatozoon canis, Hepatozoon felis, PCR
Keywords: Cat, Central Spain, Cytauxzoon sp., Hepatozoon canis, Hepatozoon felis, PCR